KONTRIBUSI PEMIKIRAN BUSTHANUL ARIFIN TENTANG PELEMBAGAAN HUKUM ISLAM DAN PENINGKATAN WEWENANG PENGADILAN AGAMA DALAM SISTEM HUKUM NASIONAL - Tentiyo Suharto (Universitas Islam Negeri Fatmawati Sukarno, 2016)
Indonesian national law derived from western law, customary law and Islamic law. Given the efforts to establish the institution of Islamic law in Indonesia experienced many challenges and Religious Courts institutions is still lacking in authority. Prof. Dr. H. Busthanul Arifin, SH continue to think seriously to make Islamic law as an integral part of the national legal system. In the end, he can implement his ideals. Based on the above background of this study revealed three issues, namely First, Is Arifin Busthanul contribute ideas about the institutionalization of Islamic law in the national legal system. Second, Is Arifin Busthanul thinking about the authority of the Religious Courts in the national legal system. Third, How implications Arifin Busthanul thinking on the institutionalization of Islamic law and the authority of the Religious Courts in the national legal system to the development of Islamic law in Indonesia. The purpose of this study was that Muslims know the figures that played a major role behind the enactment of Law Number. 7 Year 1989 regarding the enactment of the Religious and Islamic Law Compilation (KHI).Theoretical studies in this research is the theory of the formation of the institutionalization of Islamic law, the theory of the relation between religion and state law and political theory. This research is a research study of character with the historical approach, the approach of the Act, the conceptual approach, and the comparative approach and data analysis techniques using inductive method. The results of this study explains that Islamic law referred to and determined by the legislation can apply directly without going through traditional law, the Republic of Indonesia (the Government) can set something of a problem in accordance with Islamic law, all the settings that apply only to the followers of Islam and results Busthanul Arifin contribute ideas about the institutionalization of Islamic law are: 1. draft Law on Religious Courts, 2. draft Compilation of Islamic Law. Privileges Religious Courts under Act Number. 3 2006 was in the field of civil law include: marriage, inheritance wills, grants, endowments, alms, charity, donation and sharia economy. Implications of thought Busthanul Arifin against the Islamic law in Indonesia is the emergence of legislation that comes from Islamic law, for example the Law on Hajj, Zakat, Infak, Endowments, Economic Regulation Based Regional Shari’ah and religion.